INTEGRATIVE PEDAGOGY ENHANCING LEARNING THROUGH HOLISTIC APPROACHES - Dilfuza Madgafurova (Galaxy International Interdisciplinary Research Journal, 2024)
Integrative pedagogy is an instructional approach that recognizes the interconnectedness of knowledge and promotes a holistic understanding of subjects by integrating various disciplines, perspectives, and learning experiences. This article explores the concept of integrative pedagogy, its theoretical foundations, and its practical applications in educational settings. Drawing from research and best practices, we highlight the benefits of integrative pedagogy in fostering critical thinking skills, promoting interdisciplinary understanding, and preparing students for real-world challenges. Furthermore, we discuss strategies for implementing integrative pedagogy, including curriculum design, teaching methods, and assessment techniques. By adopting integrative pedagogy, educators can create dynamic learning environments that encourage students to make meaningful connections, develop a broad range of skills, and become lifelong learners.